2011
DOI: 10.1103/physrevlett.107.017204
|View full text |Cite|
|
Sign up to set email alerts
|

Spin Interactions in bcc and fcc Fe beyond the Heisenberg Model

Abstract: Usually, the adiabatic magnetic exchange-energy hypersurface is parametrized in terms of the bilinear Heisenberg interactions in pairs of atoms. For general magnetic configurations, this model is not complete even if it includes pairs with up to infinite interatomic distances. In contrast, the modeling by an in principle infinite spin-cluster expansion is complete for all conceivable magnetic configurations. In the present Letter, it is shown for bcc and fcc iron that a very accurate representation can be reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…It is therefore unsurprising that in metallic magnetic materials such interactions cannot be only described in simple pairwise terms, but must also include interactions over groups of sites. Many authors in the past have found theoretical evidence of the existence and importance of terms beyond a simple Heisenberg picture [44][45][46][47][48] . An indication of their presence follows directly from the calculation of effective pairwise interactions which adopt different values when evaluated from different magnetic states.…”
Section: A Hierarchy Of Local Moment Correlationsmentioning
confidence: 99%
“…It is therefore unsurprising that in metallic magnetic materials such interactions cannot be only described in simple pairwise terms, but must also include interactions over groups of sites. Many authors in the past have found theoretical evidence of the existence and importance of terms beyond a simple Heisenberg picture [44][45][46][47][48] . An indication of their presence follows directly from the calculation of effective pairwise interactions which adopt different values when evaluated from different magnetic states.…”
Section: A Hierarchy Of Local Moment Correlationsmentioning
confidence: 99%
“…With the advent of high performance computational resources, advanced first-principles techniques can now be applied to study the magnetic and electronic structure of Fe at elevated temperature. These include the dynamical mean field theory (DMFT) [5,[8][9][10][11][12][13][14], Hubbard models [15], the dynamical coherent potential approximation [16], extended Heisenberg models based on parameters calculated with density functional theory [17][18][19][20][21], spin cluster expansions [22][23][24], or spin-fluctuation theory [6]. For an overview of the recent advances in this field see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The approach described here is aimed at finding the most relevant part of the space of spin configurations, and to evaluate as accurately as possible the interatomic exchange interaction here. This is different from the approach of spin-cluster expansions that aim at introducing sufficiently many terms (of the order of several 30-50) in an expansion of the exchange energy [23], so that a good description of any possible configuration could be obtained, albeit without self-consistency of the atomic spin system. Whether cluster expansions, or the approach proposed here, is better suited to in general describe the dynamics of magnetic materials becomes a numerical exercise where the two different methods should be compared in how they reproduce a large body of experimental finitetemperature data.…”
mentioning
confidence: 95%